The Raven Boys [compact disc, unabridged] - Stiefvater, Maggie, 1981- (Stiefvater, Maggie, 1981- Raven cycle, 2012)
Though she is from a family of clairvoyants, Blue Sargent's only gift seems to be that she makes other people's talents stronger, and when she meets Gansey, one of the Raven Boys from the expensive Aglionby Academy, she discovers that he has talents of his own--and that together their talents are a dangerous mix.